2020
DOI: 10.1002/eat.23249
|View full text |Cite
|
Sign up to set email alerts
|

Identifying duration criteria for eating‐disorder remission and recovery through intensive modeling of longitudinal data

Abstract: ObjectiveOutcome states, such as remission and recovery, include specific duration criteria for which individuals must be asymptomatic. Ideally, duration criteria provide predictive validity to outcome states by reducing symptom‐return risk. However, available research is insufficient for deriving specific recommendations for remission or recovery duration criteria for eating disorders.MethodWe intensively modeled the relation between duration criteria length and rates of remission, recovery, and subsequent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…There is currently no consensus on the definition of recovery of eating disorders. De Young et al recently recommended that 6 months be used for recovery definitions of bulimia ( 17 ), whereas DSM-V classification provides unspecific guidance, i.e., « criteria not met for a sustained period of time » ( 1 ). Richmond et al reported four items for eating disorders recovery definition according to patients, parents and clinicians: (a) psychological well-being, (b) eating-related behaviors/attitudes, (c) physical markers, and (d) self-acceptance of body image ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no consensus on the definition of recovery of eating disorders. De Young et al recently recommended that 6 months be used for recovery definitions of bulimia ( 17 ), whereas DSM-V classification provides unspecific guidance, i.e., « criteria not met for a sustained period of time » ( 1 ). Richmond et al reported four items for eating disorders recovery definition according to patients, parents and clinicians: (a) psychological well-being, (b) eating-related behaviors/attitudes, (c) physical markers, and (d) self-acceptance of body image ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous definitions of therapy-resistant eating disorders (EDs) can be found in the literature, and the terms "chronic", "long-lasting ED" and "Severe and Enduring ED" (SE-ED), have been used interchangeably (Young et al, 2020). However, the precise parameters of severity and duration are uncertain (Robinson, 2009;Touyz et al, 2013), for example, what are the markers of severity (specific-general psychopathological symptomatology, frequency of abnormal eating behaviours in the case of bulimia nervosa (BN) and binge eating disorder [BED]) or weight (in the case of anorexia nervosa [AN], although applied in Diagnostic and Statistical Manual of Mental Highlights � Almost a half of people with anorexia nervosa (AN) and binge eating disorder (BED) had a good response to treatment, whereas for bulimia nervosa (BN) and other specified feeding and eating disorder (OSFED) only a quarter attained this outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the primacy of symptom remission and increasing emphasis on social and interpersonal factors, the clinical literature on eating disorders offers definitions of recovery that indicate particular timeframes during which behaviours must remit before “recovery” can be said to occur. Common timeframes range from six to eighteen months depending on whether one is looking at symptom composites (assessment across a collection of symptoms) or individual symptoms (such as bingeing, purging, or restriction, assessed individually) (De Young et al, 2020). Many of the clinical definitions of recovery, including Bardone-Cone et al's (2010) definition, offer transdiagnostic 3 conceptualizations of recovery, arguing that that is both more practical (as people may experience diagnostic crossover and different symptoms at different points in time) and clearer to communicate (Bardone-Cone et al, 2018).…”
Section: Defining Eating Disorder Recoverymentioning
confidence: 99%
“…Bardone-Cone et al (2010) in particular have developed a clear and thorough set of criteria for recovery that take into account physical (e.g., weight restoration, nutritional stabilization), behavioural (e.g., restricting, binge, and purge behaviour), cognitive (e.g., disruptive, obsessive, and intrusive thoughts), and psychological (e.g., mood, anxiety) factors. Often, definitions of recovery from eating disorders begin with the requirement of symptom remission (De Young et al, 2020), though this alone is often seen as insufficient for determining recovery (Wade & Lock, 2020). Recovery definitions can also integrate social factors, attending to how people interact with others (Bachner-Melman et al, 2006) and to their overall quality of life (de Vos et al, 2017).…”
Section: Defining Eating Disorder Recoverymentioning
confidence: 99%